The Legal Status of Land Formed by Sedimentation and Lake Filling from the Perspective of the State’s Right of Control - Lumasia; Henry Soelistyo Budi; Endang Pandamdari (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The increasing emergence of land formed through natural sedimentation and artificial lake filling has generated significant legal uncertainty regarding its ownership status and management under Indonesian land law. This issue becomes particularly complex when such land is claimed by private individuals despite its formation occurring within areas previously controlled by public water bodies. Accordingly, this study addresses two principal questions: (1) What is the legal status of land formed by sedimentation and lake filling under Indonesian land law? and (2) How should the State’s Right of Control be interpreted in determining rights over such land? This research employs a normative juridical method using statutory, conceptual, and case approaches. Legal materials are analyzed through qualitative legal interpretation to examine the relationship between land formation processes and the constitutional doctrine of the State’s Right of Control as stipulated in Article 33 paragraph (3) of the 1945 Constitution and relevant agrarian regulations. The findings reveal that land created through sedimentation and lake filling cannot automatically become private property merely because of physical occupation or utilization. Such land initially falls within the scope of the State’s Right of Control, as it constitutes newly emerged land resulting from natural or artificial geographical changes. The state possesses the authority to regulate, allocate, and determine legal rights over the land while ensuring public welfare, environmental sustainability, and legal certainty. This study contributes to the development of agrarian law theory by clarifying the legal construction of newly emerged land and proposing a more coherent interpretation of the State’s Right of Control to resolve ownership disputes and strengthen legal certainty in the management of sedimentation and reclaimed lands in Indonesia